Immunogenicity of HIV-1 Env mRNA and Env-Gag VLP mRNA Vaccines in Mice - Qi Ma; Jing Yang; Xiaoguang Zhang; Hongxia Li; Yanzhe Hao; Xia Feng (Vaccines)
Background: The development of a protective vaccine is critical for conclusively ending the human immunodeficiency virus (HIV) epidemic. Methods: We constructed nucleotide-modified mRNA vaccines expressing HIV-1 Env and Gag proteins. Env–gag virus-like particles (VLPs) were generated through co-transfection with env and gag mRNA vaccines. BALB/c mice were immunized with env mRNA, env–gag VLP mRNA, env plasmid DNA vaccine, or lipid nanoparticle (LNP) controls. HIV Env-specific binding and neutralizing antibodies in mouse sera were assessed via enzyme-linked immunosorbent assay (ELISA) and pseudovirus-based neutralization assays, respectively. Env-specific cellular immune responses in mouse splenocytes were evaluated using an Enzyme-linked immunosorbent assay (ELISpot) and in vivo cytotoxic T cell-killing assays. Results: The Env-specific humoral and cellular immune responses elicited by HIV-1 env mRNA and env–gag VLP mRNA vaccine were stronger than those induced by the DNA vaccine. Specific immune responses induced by the env mRNA vaccine were significantly stronger in the high-dose group than in the low-dose group. Immunization with co-formulated env and gag mRNAs elicited superior cellular immune responses compared to env mRNA alone. Conclusions: These findings suggest that the env–gag VLP mRNA platform holds significant promise for HIV-1 vaccine development.